The Scientific Heritage of Shihobiddin Suhrawardi And His Role In Philosophy and Sufism - Bakhriddinovich, Murtozaev Shahobiddin (Buletin Antropologi Indonesia, 2024)
In this article, the scientific legacy of the great Islamic scholar and philosopher Shihab al-Din Suhrawardi, along with his unique position in the fields of philosophy and sufism, is analyzed, highlighting how his views had a profound impact on Eastern philosophy and Sufism. Additionally, the article examines Suhrawardi’s major scholarly works, their content, and the main directions of his teachings, while also exploring his distinctive approaches to spiritual elevation and issues related to human spirituality through the philosophical system he developed.